Going down to the crossroads: popular music and transformative magic. Issue 2 (May 2020) - Angus, Bill
Abstract : If there is a single narrative that captures the modern understanding of transformative crossroads magic it is the spurious fable of the selling of Robert Johnson's soul. When, in the palaeoanthropology of 20 th century rock and roll music, the biographers of the short-lived blues legend claimed that he had been down to the Dockery Plantation crossroads at midnight to sell his soul to the Devil in exchange for guitar skills, they were perhaps unwitting witnesses to the deep history of myth and ritual that has long been associated with the transformative space of the crossroads. They were not lacking in foresight, however, about the way in which such a claim would enhance their subject's credibility. The value of such a sulphurous reputation for a musician is not merely a recent phenomenon but also has historical precedents. A hundred years before Johnson (who lived 1911–1938), the guitarist and violinist Niccolo Paganini (1782–1840) was considered such a suspiciously devilish virtuoso that his audiences were reputed to cross themselves before his concerts in hope of protection from subtle demonic influence. One audience member even fled a concert after reporting seeing the Devil himself aiding Paganini's performance. Going a little further back, Giuseppe Tartini (1692–1770) explained of his best-known sonata, The Devil's Trill (1713), that he had 'written down the piece after waking from a particularly vivid dream of the Devil playing a violin with ferocious virtuosity', and claimed that it was 'but a shadow of what he had witnessed in the dream, for he was unable to capture on the page the Devil's full intensity'. His long career was certainly not harmed by this youthful excursion into Hell.